Nonconsensual Sexual Experience Histories of Incarcerated Men: A Mixed Methods Approach - McKie, Raymond M. (International journal of offender therapy and comparative criminology, 2024)
Nonconsensual sexual experiences (NSEs) may contribute to mental health concerns among incarcerated individuals, yet NSEs are understudied in this population. This study takes a novel approach in examining the prevalence of NSEs among incarcerated males by utilizing both quantitative and qualitative measures. The sample consisted of 189 men from three provincial maximum-security prisons in Ontario, Canada. Based on quantitative findings, 44.2% of the sample experienced NSEs before the age of 18, and 41.7% of the sample endorsed an experience that fit the legal definition of a NSEs as adults. Participants also responded to a qualitative open-ended question about their history of NSEs. Based on qualitative findings, a total of 23% of the men reported at least one incident of a NSE (e.g., child and adult). Based Findings highlight the high prevalence of NSEs among incarcerated men with quantitative responses demonstrating how the use of a behavioral questionnaire may, to some extent, correct for underreporting of NSEs. Qualitative responses illustrate the lived experience of incarcerated men and provide a deeper understanding of their NSEs. Responses also speak to the lack of resources and support available to these men. Findings underscore the need for proactive approaches in meeting mental health needs of incarcerated men in general and with regard to NSEs in particular. Results may inform the development of future correctional procedures (i.e., intake protocols that account for men with NSEs) and resources to support incarcerated men in navigating the psychological impact of non-consensual sexual experiences.